2016
DOI: 10.1002/btpr.2248
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a bacterioruberin‐producing Haloarchaea isolated from the marshlands of the Odiel river in the southwest of Spain

Abstract: In this work, we describe the isolation, identification, pigment characterization, and optimization of the culture conditions for a haloarchaea strain isolated from salt evaporation ponds in the Odiel river, at Southwest of Spain. The haloarchaea belongs to the genus Halorobrum, as deduced from the analysis of its 16S rRNA encoding gene and has been designated as Halorubrum sp. SH1. The growth conditions for the new strain were optimized studying temperature, NaCl concentration, agitation rate and light intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 46 publications
2
30
1
Order By: Relevance
“…The identification and composition of C-50 carotenoids in strain Haloterrigena sp. SGH1 was based on the data analyses of their chromatographic migrations, UV-Vis spectra, spectral fine structure and MS fragmentation patterns (Fong et al, 2001;Mandelli et al, 2012;De la Vega et al, 2016). The absorbance spectrum of the methanol extract of strain SGH1 showed the photometric fingerprint or three-fingered maxima profile that include maxima at 468, 494, and 526 nm (Figure 3), as it has been previously reported in archaea (Mandelli et al, 2012; Results are shown as mean ± standard error with n values in parentheses.…”
Section: Strain Sgh1mentioning
confidence: 64%
See 3 more Smart Citations
“…The identification and composition of C-50 carotenoids in strain Haloterrigena sp. SGH1 was based on the data analyses of their chromatographic migrations, UV-Vis spectra, spectral fine structure and MS fragmentation patterns (Fong et al, 2001;Mandelli et al, 2012;De la Vega et al, 2016). The absorbance spectrum of the methanol extract of strain SGH1 showed the photometric fingerprint or three-fingered maxima profile that include maxima at 468, 494, and 526 nm (Figure 3), as it has been previously reported in archaea (Mandelli et al, 2012; Results are shown as mean ± standard error with n values in parentheses.…”
Section: Strain Sgh1mentioning
confidence: 64%
“…Lorantfy et al, 2014; De la Vega et al, 2016). This was a preliminary evidence for the presence of BR-type molecules in SGH1 and the presence of a BR-type molecule in strain SGH1 cells was confirmed by Raman spectroscopy (Table 4) which showed three major Raman displacement signals (1.502, 1.147, and 995 cm −1 ) that were in close proximity with those informed for extracts from other haloarchaea (Jehlička et al, 2014;Dina et al, 2017).…”
Section: Strain Sgh1mentioning
confidence: 64%
See 2 more Smart Citations
“…11 With the exception of our previous study reported recently, 6 to the best of our knowledge, there are two articles that describe carotenoid production from a Halorubrum strain. 12,13 Urmia Lake is the largest brine lake in the Middle East and the second-largest saltwater lake in the earth. 14 Even so, very few studies of the lake have been reported, and no study was published on the carotenoidproducing prokaryotics that live in this hyper-saline lake.…”
Section: Introductionmentioning
confidence: 99%